The garlic-derived organosulfur compound diallyl trisulphide suppresses tissue factor function. Issue 3 (13th January 2022) - Okue, Sachiko; Yaguchi, Manami; Miura, Atsushi; Ozaki-Masuzawa, Yori; Hosono, Takashi; Seki, Taiichiro
Abstract : DATS, a characteristic flavor component derived from garlic, inhibits tissue factor (TF) function and ameliorates plaque formation. DATS may serve as a dietary constituent that exerts beneficial effects on vascular diseases including atherosclerosis. Abstract : Tissue factor (TF) is a critical initiator of extrinsic coagulation that sometimes causes thromboembolism. Diallyl trisulphide (DATS) is a secondary metabolite of allicin generated in crushed garlic, with various pharmacological effects. This study aimed to clarify the effect of DATS on the extrinsic coagulation elicited by TF and arteriosclerosis. TF activity was measured using a clotting assay in TF-expressing HL60 cells. DATS inhibited TF activity in a dose-dependent manner. TF expression in TNF-α-stimulated human umbilical vein endothelial cells was examined using real-time PCR and western blotting. DATS inhibited TF mRNA and protein expression induced by TNF-α via inhibition of JNK signalling. The effect of DATS on arteriosclerosis was also examined in apolipoprotein E-deficient mice. DATS administration in these mice tended to decrease atherosclerotic lesion size. These results strongly suggest that DATS prevents thromboembolism triggered by atherosclerosis via the inhibition of plaque formation and TF function.